PENYULUHAN UPAYA PERINGATAN DINI DAN TANGGAP DARURAT TERHADAP BENCANA - Multilawati Nasution; Ahmad Syapawi; Sheragizca Yolanda Situmeang (Politeknik Negeri Sriwijaya, 2024)
Flood disasters represent a serious threat to communities in various regions of Indonesia. One effort to anticipate floods is by conducting community outreach regarding established guidelines for early warning and emergency response. The early warning guidelines include early warning systems, risk identification, communication and education, preparedness training, and evaluation of lessons learned. This community service activity aims to provide knowledge to the community and to remind them to remain concerned about their surrounding environment in order to prevent flood disasters. The method used by the research team was to conduct field counseling by gathering several residents of RT 053, Bukit Lama Subdistrict. The counseling delivered material on early emergency response to flood disasters. This community service activity is expected to be implemented by residents when floods occur in residential areas, thereby significantly reducing potential losses.